Dysbiosis of Gut Microbiome in Neonatal Sepsis - A Prospective Study - Vijay, D.Danis; D. Caroline, D. Caroline; A. Sujhithra, A. Sujhithra; shilpa, Antinate; N. Harish, N. Harish; S. Jayanthi, S. Jayanthi; Ravi, Vidhya (Journal of Neonatal Surgery, 2025)
Background information: Sepsis is a life-threatening condition, and sepsis in newborn babies is called neonatal sepsis. The highest rate of sepsis among newborns is found in India. The gut microbiome is crucial to maintaining health and the development of disease. So, the study aims to analyze the gut microbiome of infants with neonatal sepsis. Methodology: Three faecal samples were collected from neonates with clinical signs and symptoms of sepsis and processed. Metagenomic DNA was extracted using a Qiagen stool DNA extraction kit. Amplification of the bacterial 16SV3-V4 region was carried out. 16S Microbiome Profiling was performed. Cluster Generation and Sequencing were done. Bioinformatics analysis was performed to process the data of the samples. A comparative study of the samples was conducted at different taxonomic levels. Results: Most abundant species in the samples were identified as unclassified species from the genus Enterococcus (40.18%), unclassified species from the genus Streptococcus (32.66%) and unclassified species from the family Enterobacteriaceae (15.17%), respectively. The results correlated with blood culture findings. Conclusion: The genera of the causative organism in neonatal sepsis correlate to the most prevalent bacteria in the gut microbiome. Sepsis may be due to a gut-derived bacterial translocation phenomenon and requires novel strategies for prevention.